Attitudes and motivation in early foreign language learning - Mihaljević-Djigunović, Jelena (Array, 2012)
This paper focuses on young foreign language learners’ attitudes and motivations. An overview is given of the main issues in this research area, based on key European studies. Approaches to studying these affective learner characteristics are described. Some attention is devoted to data elicitation techniques and the importance of triangulation. Research findings are presented through overviews of cross-sectional and longitudinal studies carried out in different European settings. The latter are presented in more detail, because their findings seem to be more revealing of the early foreign language learning process. The overall conclusion of this review paper is that young foreign language learners’ attitudes and motivations are not stable learner characteristics but change over time, creating layers of complexity that warrant further research. Suggestions about possible future directions in researching young foreign language learner attitudes and motivations, and the application of its findings are also made.